Роль «внутреннего права» международных неправительственных организаций в определении правового статуса международных неправительственных организаций - Аскерова, Э.Г. кызы (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
In the article were represented establishments, notions, main features, structure, duties, activities direction of international non - governmental organization were guided diversity of available idea in international law and international practice. The differing features between NGO's and the traditional participants of international law states were broadly analyzed.